Bioactive Potential of Marine Biota (Algae, Sponges, and Marine Bacteria) as a Source of Antimicrobial Compounds - Wahyuni, Sri; Mursawal, Asri; Kurniawan, Ronal (South East Asian Marine Sciences Journal, 2025)
Antimicrobial resistance has become one of the most serious global health threats, prompting the search for new natural sources of antibiotics. Marine biota, such as algae, sponges, and bacteria, are known to produce a variety of secondary metabolites with potential biological activity, particularly as antimicrobial compounds. This review article examines the bioactive potential of these marine biota as an alternative source of natural antibacterial compounds. The study was conducted by reviewing various international and national literature related to the bioactive metabolites produced, their mechanisms of action against pathogenic bacteria, and the potential for their use in developing new antibacterial agents. The results of the review indicate that sulfated polysaccharides, terpenoids, alkaloids, and phenolic compounds from algae; alkaloids, cyclic peptides, and terpenoids from sponges; and secondary metabolites of marine symbiont bacteria have significant antibacterial activity, including against antibiotic-resistant bacteria. However, the development of marine bioactive compounds still faces various obstacles, particularly related to isolation techniques, mass production, and environmental sustainability issues. Therefore, modern biotechnological approaches, such as genomics, metabolomics, and synthetic biology, are needed to optimize the utilization of these marine resources. This article confirms that marine biota are important candidates for the development of new, sustainable antibacterial agents and have the potential to support the strengthening of the blue economy concept.